Synthesis, characterization and solid-state properties of [Zn(Hdmmthiol)2]•2H2O complex - Dagdelen, Fethi; Aydogdu, Yildirim; Dey, Kamalendu; Biswas, Susobhan (Springer Heidelberg, 2016)
The zinc(II) complex with tridentate thiohydrazone ligand have been prepared by metal template reaction. The metal template reaction was used to prepare the zinc (II) complex with tridentate thiohydrazone ligand. The reaction of diacetylmonoxime and, morpholine N-thiohydrazidewith Zn(OAc)(2)center dot 2H(2)O under reflux yielded the formation of the [Zn(Hdmmthiol)(2)]center dot 2H(2)O complex. The complex was characterized by a combination of protocols including elemental analysis, UV+vis, FT-IR, TG and PXRD. The temperature dependence of the electrical conductivity and the optical property of the [Zn(Hdmmthiol)(2)]center dot 2H(2)O complex is called H(2)dammthiol was studied. Powder X-ray diffraction (PXRD) method was used to investigate the crystal structure of the sample. The zinc complex was shown to be a member of the triclinic system. The zinc complex was determined to have n-type conductivity as demonstrated in the hot probe measurements. The complex was determined to display direct optical transition with band gaps of 2.52 eV as determined by the optical absorption analysis.
Keywords: Schiff-Base; Electrical-Conductivity; Biological-Activity; Optical-Properties; Metal-Complexes; Phenylmercury(Ii); Nickel(Ii); Ligands; Zn; Ni